Oral Language Abuse In Teaching-Learning Activity At Kabupaten Sumba Tengah Elementary School - Sabarua, Jefrey Oxianus; Wote, Alice Yeni Verawati (Universitas Pendidikan Ganesha, 2018)
This research bacground based on student’s field experience of unsecure, oppressed, and fearful feelings caused by teacher’s utterances in class teaching learning activities. The objectives of this researh are: to identify the lingual form of lingulistic units inside teacher’s verbal violence/oral language abuse, to find teacher’s verbal violence/oral abuse expressions, and to identify factors causing verbal violence or verbal harassment or oral language abuse done by teachers in Kabupaten Sumba Tengah. The method used is descriptive qualitative method. The data gathering method/data gathering technique uses “Simak and Cakap Method” (Observing and Conversing Methods) and analyzed using “Agih and Padan Method”. The result of this study showed that verbal violence/verbal abuse are manifested in the lingual forms of linguistic units as words, phrases and sentences. The form of linguistic language tends to appear as exclamation sentences. Forms of verbal violences expressed by snaping, ignoring, uderestimating, humiliating in front of public/others, and doing accusations. Expressions tends to be manifested in the forms of accusations and humiliations toward children in front of others/public. The factors causing verbal abuse are education culture herritage of the past, teacher’s lack of knowledge on verbal abuse, teacher’s lack of vocubularies, their administrative tasks demands, discipling efforts, and local culture